Fostering Partnerships between Public Health Functions within Health and Social Services Organizations: A Perspective from the Province of Quebec (Canada) - Mélissa Généreux; Linda Pinsonneault; Mathieu Roy (Journal of Preventive Medicine And Care, 2016)
Health and social services organizations discriminate too much between core public health functions. Health protection actions, services, and programs are often separate from those concerned with disease prevention and health promotion. In this comment, we advocate for more partnerships between all public health functions within health and social services organizations. Stronger bridges between such teams, services, and programs are needed to move forward with a more encompassing and integrated perspective aiming for social justice and equity. In this comment, we support this position with some examples. We also use smoking-related issues from a regional representative population-based sample (Eastern Townships, Quebec, Canada) to demonstrate how we can better struggle against social inequalities with a perspective that simultaneously considers all functions of public health within actions, services, and programs of health and social services organizations. We conclude with avenues to foster such partnerships.
Keywords: Health services administration